2019
DOI: 10.21315/eimj2019.11.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Students, Staff and Simulated Patients towards Objective Structured Clinical Examination (OSCE)

Abstract: Objective Structured Clinical Examination (OSCE) has been widely used to assess the clinical performance of medical and health profession students. The literature has revealed that OSCE is an effective evaluation tool for evaluating the clinical skills of medical students. The objectives of this study were to investigate perception of the students and staff of OSCE as a clinical assessment tool during their clinical years at the Faculty of Medicine, Suez Canal University (FOM-SCU) as well as the perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…The OSCE will provide a valid, standardized, and reliable clinical exam. It is the golden exam in most of the postgraduate degrees [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OSCE will provide a valid, standardized, and reliable clinical exam. It is the golden exam in most of the postgraduate degrees [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foud et al [18] from Egypt investigated perception, among the clinical year students and staff, of OSCE as a clinical assessment tool during their clinical years through different questionnaires. They reported that OSCE is a valuable practical learning experience and most of the students agreed that OSCE helped them to identify gaps in their clinical knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty eight percent of the students agreed that OSCE should remain as a form of performance assessment, and 83% of them agreed that OSCE was a valuable practical exam and provided them a great learning experience. Approximately 80.4% of the staff emphasized that faculty members need specific training to achieve more valid and reliable results when using OSCE as an assessment tool, and 76.5% of them agreed that using OSCE reduced the bias in clinical assessment [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is the golden exam in most of the postgraduate degrees. 25,26 Adding another important point to the fairness and objectivity of the exam, the study suggested the use of a standardized setting as the national license exam is considered to be highstakes one. The criterion-referenced standard is preferred for theoretical and clinical parts of the exam.…”
Section: Discussionmentioning
confidence: 99%